1994
DOI: 10.1128/aem.60.11.4116-4123.1994
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Dissolved Nitrogen by Heterotrophic Bacterioplankton: a Comparison of Three Ecosystems

Abstract: The contributions of different organic and inorganic nitrogen and organic carbon sources to heterotrophic bacterioplankton in batch cultures of oceanic, estuarine, and eutrophic riverine environments were compared. The importance of the studied compounds was surprisingly similar among the three ecosystems. Dissolved combined amino acids (DCAA) were most significant, sustaining from 10 to 45% of the bacterial carbon demands and from 42 to 112% of the bacterial nitrogen demands. Dissolved free amino acids (DFAA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 42 publications
(48 reference statements)
5
39
0
Order By: Relevance
“…The observed bacterial preference for DFAA over DCAA agrees with other studies [36,37], but a higher preference for DFAA over ammonium [38] was not con¢rmed by our observations. The large uptake of ammonium in the hypolimnion samples may be related to utilization of carbohydrates, together creating a favourable C/N ratio for bacterial cell production [39,40].…”
Section: Relations Between Bacterial Production and Uptake Of Speci¢csupporting
confidence: 86%
“…The observed bacterial preference for DFAA over DCAA agrees with other studies [36,37], but a higher preference for DFAA over ammonium [38] was not con¢rmed by our observations. The large uptake of ammonium in the hypolimnion samples may be related to utilization of carbohydrates, together creating a favourable C/N ratio for bacterial cell production [39,40].…”
Section: Relations Between Bacterial Production and Uptake Of Speci¢csupporting
confidence: 86%
“…5) may be related to the dominance of Bacteroidetes bacteria in summer in this area. Bacteroidetes are considered as specialist bacteria that prefer HMW organic matter (Cottrell and Kirchman, 2000;Elifantz et al, 2005), which contains a significant amount of proteins and polypeptides (Coffin, 1989;Rosenstock and Simon, 1993;Kroer et al, 1994;Keil and Kirchman, 1999). Thus, in the short term, the CS community would be well prepared to process the organic matter resulting from bacterial growth and protozoan grazing.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between substrate pool size, hydrolysis rates, and product uptake were also made by Hoppe et al (1988) in a study of the utilization of dissolved combined amino acids by nearshore bacterioplankton, and by Miinster ( 199 1) in a comparative study of glucose and amino acid utilization by bacteria in eutrophic and polyhumic lakes. In a broader survey, Kroer et al (1994) found that specific Leuaminopeptidase activities were similar among marine, estuarine, and riverine bacterioplankton despite wide differences in the concentration of inorganic N. Many studies, in both aquatic and terrestrial systems, have documented inverse relationships between phosphorus availability and phosphatase activity (e.g. Ammerman 1991;Cotner and Wetzel 1991;Mulholland and Rosemond 1992); in some instances, this activity has been used as an indicator of P availability (Wctzel 198 1;Gage and Gorham 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Among ecosystems, bacterial production can be correlated with DOC concentration or, more indirectly, with primary production (Cole et al 1988). Within an ecosystem the trophic basis of bacterial production is more difficult to discern (Findlay et al 1991), partly because other physicochemical [UV radiation (Herndl et al 1993), nutrients (Meyer-Reil 1987), temperature (Hudson et al 1992;Shiah and Ducklow 1994)] and biological factors [grazing (Gonzalez et al 1990;Bott and Kaplan 1990), growth efficiency (Kroer 1993;Biddanda et al 1994)] play a role in regulating productivity. Also, because DOC is a heterogeneous mix of compounds, gross abundance does not equate with biodegradability.…”
mentioning
confidence: 99%